Pushing boundaries in the measurement of language attitudes: Enhancing research practices with the L’ART Research Assistant app - Breit, Florian; Tamburelli, Marco; Gruffydd, Ianto; Brasca, Lissander (LingBaW. Linguistics Beyond and Within, 2024)
The importance of methodological developments has recently been emphasised both in language attitude research specifically (Kircher & Zipp 2022), and across linguistics and the social sciences more broadly, where there has been a particular focus on replicability (Sönnig & Werner 2021; Kobrock & Roettger 2023). One aspect of this concerns the adoption of more open, consistent, and comparable implementations of method. We introduce a new digital application (the L’ART Research Assistant) for research in multilingualism and language attitudes. Designed specifically for work with populations speaking a majority and a regional/minority/minoritised/heritage language, the app implements reference versions of some common research methods and tasks. This benefits the research community by enhancing consistency and comparability within and across studies and by improving replicability and reproducibility. We discuss technical and methodological considerations behind the app and illustrate its use with a brief case study of language attitudes across three European communities whose regional/minority languages receive radically different degrees of socio-political recognition: Lombard (Italy), Moselle-Franconian (Belgium), and Welsh (UK). The case study demonstrates not only how the app facilitates research across different communities that is easily comparable, results also reveal fundamental differences in attitude scores depending on the methods employed (AToL v. MGT). Consequently, we argue that there is a need to move toward both the adoption of more consistent, comparable methods as well as toward a more holistic approach to measuring language attitudes, where a battery of tests — as opposed to a single measure — should become the norm.